Quantification methods of spinal and supraspinal excitability during cross-country skiing: a pilot study on skiing-specific motor control measurements - Lindinger, S.; Piitulainen, H.; Karczewska-Lindinger, M.; Giangrande, A.; Piirainen, J. M. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Motor control is an essential part of athlete`s efficient performance. The motor control can be divided to spinal and supraspinal components, which`s contribution can be quantified using Hoffmann-reflex (H-reflex) and volitional wave (V-wave) methods, respectively, during both isometric (Aagaard et al. 2002) and dynamic conditions (Alkjaer et al. 2013). However, it is unknown how feasible these responses would be to study more challenging multi-joint dynamic tasks like cross-country skiing. Purpose was to develop this methodology for complex skiing techniques for future examination of spinal and supraspinal control mechanisms during specific phases (e.g. gliding/balance control) related to performance level, fatigue status or other factors.